Predictors of mortality among adult people living with HIV/AIDS on antiretroviral therapy at Suhul Hospital, Tigrai, Northern Ethiopia: a retrospective follow-up study - Kebede Haile Misgina; Meresa Gebremedhin Weldu; Tewodros Haile Gebremariam; Negassie Berhe Weledehaweria; Haileslasie Berhane Alema; Yosef Sibhatu Gebregiorgis; Yonas Girma Tilahun (BMC, 2019)
Abstract Background Ethiopia is striving to achieve a goal of "zero human immune deficiency virus/acquired immune deficiency syndrome (HIV/AIDS)-related deaths." However, little has been documented on the factors that hamper the progress towards achieving this goal. Therefore, the ultimate aim of this study was to determine predictors of mortality among adult people living with HIV/AIDS on antiretroviral therapy (ART). Methods A retrospective follow-up study was employed on all adult HIV/AIDS patients who started ART between January 1 and December 30, 2010, at Suhul Hospital, Tigrai Region, Northern Ethiopia. Data were collected by trained fourth-year Public Health students using a checklist. Finally, the collected data were entered into SPSS version 16. Then after, Kaplan-Meier curves were used to estimate survival probability, the log-rank test was used for comparing the survival status, and Cox proportional hazards model were applied to determine predictors of mortality. Results The median follow-up period was 51 months (ranging between 1 and 60 months, inter-quartile range (IQR) = 14 months). At the end of follow-up, 37 (12.5%) patients were dead. The majority of these cumulative deaths, 19 (51.4%) and 29 (78.4%), occurred within 3 and 4 years of ART initiation respectively. Consuming alcohol (adjusted hazard ratio (AHR) = 2.23, 95% CI = 1.15, 4.32), low body weight (AHR = 2.38, 95% CI = 1.03, 5.54), presence of opportunistic infections (AHR = 2.18, 95% CI = 1.09, 4.37), advanced WHO clinical stage (AHR = 2.75, 95% CI = 1.36, 5.58), and not receiving isoniazid prophylactic therapy (AHR = 3.00, 95% CI = 1.33, 6.74) were found to be independent predictors of mortality. Conclusion The overall mortality was very high. Baseline alcohol consumption, low body weight, advanced WHO clinical stage, the presence of opportunistic infections, and not receiving isoniazid prophylactic therapy were predictors of mortality. Strengthening behavioral and nutritional counseling with close clinical follow-up shall be given much more emphasis in the ART care and support program.